APPLICATION OF DATA MINING BY USING A PRIORI ALGORITHM TO IMPROVE CUSTOMER PURCHASING DECISIONS AT MIKAMART BLITAR STORE - Nurul Farida; Mukh Taofik Chulkamdi; Zunita Wulansari (International Journal of Multidisciplinary Research and Literature, 2022)
Product arrangement, known as product display, is the layout or way of structuring products, especially products companies apply to attract consumers. Although one of the scopes of sales in the market is the delivery of information through galleries, storefronts require specialization and the ability to arrange products or displays following the standards and specifications of the company and the product itself. The resulting output directly affects the level of sales and information to be achieved in a store, especially in modern retail stores with a self-service format (self-service) such as minimarkets. To implement a display system, Data Mining is applied as a determinant of the layout of the merchandise. According to (Kusrini & Lutfi 2009), data mining is used to extract knowledge from databases. One of the many methods in Data Mining is the Apriori Algorithm. The a priori algorithm is a type of association rule in data mining. Association rule or association rule mining is used to find associative rules between item combinations to be used as wisdom to make decisions and provide a stock of products that consumers prefer